Study on the influence of oil-gas pressure difference on diaphragm in diaphragm compressor - Li, Fengyu; Liu, Xiaoming; Liu, Zhilong; Yu, Yang (Journal of physics. Conference series, 2025)
As one of the main components of hydrogen refueling stations, the diaphragm hydrogen compressor is an important equipment supporting the development of hydrogen energy in China. Currently, the diaphragm hydrogen compressor is facing a significant demand for improving reliability. The diaphragm is one of the vulnerable parts in diaphragm hydrogen compressors, mainly affected by the difference between hydraulic oil pressure and hydrogen pressure, which deforms and compresses hydrogen gas to achieve the operation of diaphragm hydrogen compressors. This study selected the oil gas pressure difference as the independent variable and conducted simulation research on the variation laws of equivalent stress and axial deformation of the diaphragm.